Transfer Pricing - A Synthesis: A Comment. - Ronen, Joshua (The Accounting Review, 1975)
Abstract This article presents the author's comments on the criticism of his article "Transfer Pricing for Divisional Autonomy," published in an earlier issue of the journal "The Accounting Review," as of April 1975. The author's article suggested a transfer pricing system that achieves the goal of profit maximization for the firm as a whole. The author claimed that by employing the concept of a transfer price plus subsidy or tax to account for transactions between divisions of a decentralized firm, he had shown how the divisional managers can make decisions which maximize corporate profits. Moreover, with this transfer pricing system, divisional profits reflect divisional contribution to corporate profits. The criticism of the article stated that the divisional managers will not accept the accounting reports produced as a result of transfer-pricing system as measures of autonomous divisional interaction. It also stated that the system causes inefficiencies of one division to be passed on to the selling division in terms of lower average revenue, price and profits. Therefore, the selling division may ask for the right to audit the cost records of the buying division.